Blended professionals, technology and online learning: Identifying a socio‐technical third space in higher education. (10th February 2020) - White, Steven; White, Su; Borthwick, Kate
Abstract: The idea of a 'third space' located between academic and professional domains has proven useful in exploring changing academic and professional roles in higher education, including in online learning. However, the role of technology in accounts of third space activity remains under‐explored. Drawing on research into the introduction of Massive Open Online Courses (MOOCs) at three UK higher education institutions, it is argued that both social and technical factors must be considered to understand, plan for and manage the third space roles and structures which emerge in such initiatives. This study focuses on learning designers, confirming that they act as third space 'blended professionals' in the somewhat distinctive case of MOOC development. However, it also proposes the concept of a socio‐technical third space in which blended professionals act as hubs in a metaphorical network of activity, using social and technical means to shape their own roles and those of others. Resumen: La idea de un 'tercer espacio' situado entre los dominios académicos y profesionales ha demostrado ser útil para explorar los cambiantes roles académicos y profesionales en la educación superior, incluyendo el aprendizaje en línea. Sin embargo, el papel de la tecnología en los relatos de la actividad de dicho tercer espacio sigue siendo poco explorado. Basándose en la investigación sobre la adopción de cursos abiertos masivos en línea en tres instituciones de educación superior del Reino Unido, se argumenta que se deben tener en cuenta tanto factores sociales como técnicos para comprender, planificar y gestionar las funciones y estructuras del tercer espacio que surgen en tales iniciativas. Este estudio se centra en la figura de los diseñadores de aprendizaje, confirmando que actúan como 'profesionales mixtos' del tercer espacio en el caso característico del desarrollo de los MOOC. Paralelamente, el estudio también propone el concepto de un tercer espacio socio‐técnico en el que los profesionales con competencias y responsabilidades mixtas actúan como centros de una metafórica red de actividad, utilizando herramientas sociales y técnicas para dar forma a sus propios roles y a los de los demás.